Advancing peace with nature through innovation: Launch of the CircularEconomy4Colombia Acceleration Program - Loiseau, Camille; Khader, Taija (2024)
The CircularEconomy4Colombia Acceleration Program is beginning today. Over the following four months, the selected teams will participate in specialized training and mentorship sessions aimed at strengthening their business models, scaling their innovations, and increasing their market readiness. The program will culminate in a Demo Day in the Spring of 2025, offering the teams a platform to showcase their progress in front of industry leaders, and key stakeholders, including investors.